2020
DOI: 10.3390/su12239860
|View full text |Cite
|
Sign up to set email alerts
|

Agri-Food Export Competitiveness of the ASEAN Countries

Abstract: Agri-food trade competitiveness analyses are relatively understudied in the empirical literature with many countries/regions missing. The novelty of this paper to analyze the agri-food export competitiveness patterns of the Association of Southeast Asian Nations (ASEAN), thereby aiming to fill this gap in the literature. Our research questions include which countries and products are competitive in the ASEAN region in agri-food trade; whether raw materials or processed products are more competitive; whether re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…To support this approach, the literature consists of similar papers dedicated to the study of relative trade advantages (as a form of economic competitiveness) for bulk primary raw agricultural commodities, such as cereals, in comparison with consumer-ready foods, such as the preparations of cereals. [106][107][108][109][110][111][112]. Up to a certain level, this study is similar to those dedicated to intra-industry competitiveness type of analyses [113][114][115], but particularly niched on the cereals sector.…”
Section: Methodsmentioning
confidence: 71%
“…To support this approach, the literature consists of similar papers dedicated to the study of relative trade advantages (as a form of economic competitiveness) for bulk primary raw agricultural commodities, such as cereals, in comparison with consumer-ready foods, such as the preparations of cereals. [106][107][108][109][110][111][112]. Up to a certain level, this study is similar to those dedicated to intra-industry competitiveness type of analyses [113][114][115], but particularly niched on the cereals sector.…”
Section: Methodsmentioning
confidence: 71%
“…The RCA index is an important metric for evaluating a country's competitiveness in exporting certain commodities (Liu & Gao, 2022). This method has been widely used by various researchers to measure the level of country's commodity competitiveness such as Erokhin et al (2020), Kuzmenko et al (2022), Matkovski et al (2022), Mizik et al (2020), Vu et al (2019), Wardani et al (2018), and Yemima & Novianti (2020). RCA calculates competitiveness by comparing the share of exports of a commodity in the country's total exports with the share of the same commodity exports in total world exports (Kim, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Other parts of the world were also analyzed with similar methodological tools. The case of the Association of Southeast Asian Nations (ASEAN) countries showed that productivity is only one potential source of competitiveness, but not an exclusive one [4]. A lack of adequate processing capacities seems to be a common barrier to higher competitiveness, as not only the ASEAN but also the CIS suffer from this [4,13].…”
Section: Regional and Country-level Analysesmentioning
confidence: 99%
“…The case of the Association of Southeast Asian Nations (ASEAN) countries showed that productivity is only one potential source of competitiveness, but not an exclusive one [4]. A lack of adequate processing capacities seems to be a common barrier to higher competitiveness, as not only the ASEAN but also the CIS suffer from this [4,13]. However, these country groups show a common characteristic: significant agri-food producers have higher comparative advantages and a better trade performance [13,50].…”
Section: Regional and Country-level Analysesmentioning
confidence: 99%
See 1 more Smart Citation